2018
DOI: 10.1002/jwmg.21480
|View full text |Cite
|
Sign up to set email alerts
|

Contact rates in wild boar populations: Implications for disease transmission

Abstract: Inter‐individual contacts in wildlife populations are usually highly heterogeneous. This variation translates into differential disease transmission rates between individuals, which have vital consequences for the spread, persistence, and control of infectious diseases. Wild boar (Sus scrofa) is an abundant game species across Europe that poses serious health threats to wildlife, livestock, and humans. However, factors shaping contact rates and structure in wild boar populations, key parameters in disease ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 50 publications
3
69
0
Order By: Relevance
“…Disease transmission was modeled using the force of infection equation (FOI; rate at which susceptible individuals become infected) outlined in Equation , where x i,j is the distance between the home range centroid of infectious individual i ( I i ) and susceptible individual j (S j ) (as defined by their x and y coordinates), a denotes alive individuals, b denotes infectious carcasses, d denotes direct transmission, c denotes carcass‐based transmission, β is the transmission probability that is specific to the transmission mechanism ( d or c ). To account for spatial contact behavior in wild boar (Podgórski, Apollonio, & Keuling, ), transmission probabilities were assumed to decay exponentially with distance according to the rate parameter λ (Table ). Additionally because wild boar exhibit heterogeneous contact structure due to family grouping (Pepin et al, ; Podgórski et al, ), probabilities of direct transmission and carcass‐based transmission were assumed to be more likely if contact occurred within the same family group ( β wd and β wc ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease transmission was modeled using the force of infection equation (FOI; rate at which susceptible individuals become infected) outlined in Equation , where x i,j is the distance between the home range centroid of infectious individual i ( I i ) and susceptible individual j (S j ) (as defined by their x and y coordinates), a denotes alive individuals, b denotes infectious carcasses, d denotes direct transmission, c denotes carcass‐based transmission, β is the transmission probability that is specific to the transmission mechanism ( d or c ). To account for spatial contact behavior in wild boar (Podgórski, Apollonio, & Keuling, ), transmission probabilities were assumed to decay exponentially with distance according to the rate parameter λ (Table ). Additionally because wild boar exhibit heterogeneous contact structure due to family grouping (Pepin et al, ; Podgórski et al, ), probabilities of direct transmission and carcass‐based transmission were assumed to be more likely if contact occurred within the same family group ( β wd and β wc ).…”
Section: Methodsmentioning
confidence: 99%
“…To account for spatial contact behavior in wild boar (Podgórski, Apollonio, & Keuling, ), transmission probabilities were assumed to decay exponentially with distance according to the rate parameter λ (Table ). Additionally because wild boar exhibit heterogeneous contact structure due to family grouping (Pepin et al, ; Podgórski et al, ), probabilities of direct transmission and carcass‐based transmission were assumed to be more likely if contact occurred within the same family group ( β wd and β wc ). In Equation , w denotes I i ‐S j contacts that are within the same family group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While demographic risk factors may influence exposure risk at a local scale (Figure ), spatial heterogeneity of these effects might cause them to diminish at the national scale. Previous studies have found that wild pig contact is strongly influenced by local scale factors of animal age, group membership, and distance between group home ranges (Pepin et al, ; Podgórski, Apollonio, & Keuling, ). Additionally, it is possible that strong spatial factors (e.g., climatic or ecological effects) might overshadow any demographic effects that would otherwise be observed.…”
Section: Discussionmentioning
confidence: 99%
“…While demographic risk factors may influence exposure risk at a local scale (Figure 4), spatial heterogeneity of these effects might cause them to diminish at the national scale. Previous studies have found that wild pig contact is strongly influenced by local scale factors of animal age, group membership, and distance between group home ranges (Pepin et al, 2016;Podgórski, Apollonio, & Keuling, 2018 and have home ranges that are 160% smaller than uninfected deer (Edmunds et al, 2018). This reduced activity can result in increased sampling of uninfected individuals, leading to lower estimates of prevalence (Nusser, Clark, Otis, & Huang, 2008).…”
Section: Accounting For Detection Error In Models Of Prevalencementioning
confidence: 99%